Generating societal impact from collaborations between universities and arts and culture organisations (ACOs) : Evidence from a survey of arts and culture professionals in the UK - Rossi, Federica; Baines, Ning; Wilson, Evelyn (Elsevier, 2024)
The art and cultural industries are known to generate not only important economic benefits, but also broader impacts on society. One of the ways in which they can amplify their societal impact is through their collaborations with universities, contributing to research and knowledge exchange activities that produce valuable outcomes for numerous societal stakeholders. Yet, the association between the characteristics of the collaboration and its impact is not clearly understood. Building on the framework of Collaborative Value Creation (CVC), we argue that the nature of the collaboration between university and ACO – whether it is transactional, integrative or transformational – will affect the breadth of impact generated – whether it benefits mainly the collaboration partners and/or external stakeholders. We rely on a unique, purpose-built survey of arts and culture professionals in the UK, co-designed by National Centre for Academic and Cultural Exchange (NCACE) and Arts Professional. The empirical findings confirm that different types of collaborations are associated with different breadth of impact: transactional collaborations mainly impact the ACO, integrative collaborations impact both partners, transformational collaborations impact external stakeholders. The impact on the ACO refers to direct benefit from the collaboration, rather than to the ACO's intention to engage in further collaborations; we find that the latter is negatively affected by the participation in transactional collaborations, and positively affected by the ACO's positive attitude towards collaborating. The study makes a theoretical contribution, by applying the CVC framework to a new context, and by identifying the mechanisms through which the nature of the collaboration influences the type of impact it produces. It also contributes to policy and practice by proposing a set of relevant implications.
Keywords: Arts and culture organisations (ACOs); Collaborative value creation; Impact; Collaborations; Resources; Transactions; universities; value creation